Hunting tourism a factor for economic development of hunting associations on the territory of the city of Leskovac - Pešić, Bratislav Mladen (Turizam, 2020)
The subject of this study is the impact of hunting tourism on the development of hunting associations in the territory of the City of Leskovac in Serbia. Non-experimental model of scientific research, survey, was applied in the paper, while the obtained results were processed by statistical data processing. Data are presented in tables and graphs. Observing the total number of completed questionnaires, 475 foreign tourist hunters were the dominant guests over domestic tourist hunters, accounting for 84.50% of the total number of hunting tourists in 2017, 87.1% in 2018, and 89. 8% in 2019. The income generated from the stay of hunters’ tourists was used by hunting associations for the purchase of certain game species and the modernization of hunting and technical facilities. The amount of revenue generated increased by 2.3% each year in 2018 and by 22.6% in 2019. Investments in 2017-2019 were up 20.1% in 2018 to 38.8% in 2019, while funds earmarked for wildlife procurement were significantly higher by 3.8% in 2018, and 50% in 2019. It can be concluded that hunting and hunting tourism must be focused on habitat conservation, environmental protection, and wildlife protection and a very important segment of the economic development of hunting associations and the entire territory in which hunting associations operate.